(untitled) (Research, Society and Development, 2022)
Objective: To describe information from Brazilian television news about adverse events with nursing professionals and students posted on Youtube. Methodology: Documentary study with a qualitative, descriptive and exploratory approach with Brazilian television reports. The interviews were transcribed and analyzed using the thematic content framework. Results: Those involved were female, they worked in public hospital services, in the south and southeast of Brazil and the titles and summaries of the news blamed only Brazilian nursing. To better situate the object, two thematic categories were carried out, namely: I - Titles and brief summary of Brazilian television news about adverse events and II - Pronouncements of those involved in adverse events. Final Considerations: The news had superficial, sensational content, which blamed only the nursing involved and did not address the real problem about adverse events. As a way of preventing such incidents, it is necessary to understand the phenomenon and implement the patient safety core.